Faktor-Faktor yang Mempengaruhi Hasil Belajar Geografi di kelas XI IPS SMA Negeri 2 Bayang Kecamatan Bayang Kabupaten Pesisir-Selatan - Sari, Nofita - (Pendidikan Geografi, 2014)
Education is an effort to develop the potential of formal and informalprocesses. The purpose of this research is to manage, analize,and look at whatlearning autcomes influences in geography class XI IPS SMAN 2 Bayang. Theresearch was descriptive correlational. The population of this research is all ofstudents class XI IPS at SMAN 2 Bayang about 132 students. Sampling techniquethat total sampling. Data collection techniques were used questionnaires and dataanalysis techniques used multiple linear regression. The results of this researchindicate that: 1) there are significant interest in studying the geography learningoutcomes of class IX IPS SMAN 2 Bayang, it is seen from the sig. 0.000<0.05 or tcount>t table (5.180>1.960) with the value of a contribution of 17.10%. 2) there isthe influence of the learning discipline on geography learning outcomes class XIIPS SMAN 2 Bayang,visible from sig 0.000<0.05 or t count>t table (5.365>1960)with the contribution of 18.10%. 3) there is the influence of family environmenton geography learning outcomes class XI IPS SMAN 2 Bayang,visible fromsig.0.000<0.05 or t count> t tabel (5.180>1960) with the value of a contribution of47.20%.4) there is the influence of interest in learning outcomes of class XI IPSSMAN 2 Bayang, visible from sig 0.000<0.05 or Fcount>Ftable (57,518>3.940)with the value of a contributions of 57.40%. this research can be used as areference in enhancing stimulation of the student, controlling and improvingbehavior, as well as the way perents improve educate.